2021
DOI: 10.1021/acsnano.0c09905
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Assembled Cobalt Oxynitride Nanorods and N-Doped Carbon Nanofibers for Efficient Bifunctional Oxygen Electrocatalysis with Exceptional Regenerative Efficiency

Abstract: Oxygen-based electrocatalysis is an integral aspect of a clean and sustainable energy conversion/storage system. The development of economic bifunctional electrocatalysts with high activity and durability during reversible reactions remains a great challenge. The tailored porous structure and separately presented active sites for oxygen reduction and oxygen evolution reactions (ORR and OER) without mutual interference are most crucial for achieving desired bifunctional catalysts. Here, we report a hybrid compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…19,20 (2) Due to the nanoscale confinement effect, the NiFe (oxy)hydroxides and NiCo (oxy)hydroxides generated on the surface of NiFe and NiCo nanoalloys are extremely thin (1− 5 nm), which neither hinder the migration of electrons in the OER process nor affect the adsorption/desorption of the intermediate products on NiFe and NiCo alloys in the catalytic process. 21,22 In addition, NiFe and NiCo alloys have high conductivity, which are beneficial for efficient electron transfer in catalytic processes. (3) A CNT as the support of these composite catalysts, which is a good electric conductor, can avoid the agglomeration of nanoparticles.…”
mentioning
confidence: 99%
“…19,20 (2) Due to the nanoscale confinement effect, the NiFe (oxy)hydroxides and NiCo (oxy)hydroxides generated on the surface of NiFe and NiCo nanoalloys are extremely thin (1− 5 nm), which neither hinder the migration of electrons in the OER process nor affect the adsorption/desorption of the intermediate products on NiFe and NiCo alloys in the catalytic process. 21,22 In addition, NiFe and NiCo alloys have high conductivity, which are beneficial for efficient electron transfer in catalytic processes. (3) A CNT as the support of these composite catalysts, which is a good electric conductor, can avoid the agglomeration of nanoparticles.…”
mentioning
confidence: 99%
“…CeO 2 /Co 4 N still possesses an overpotential of 336 mV at 10 mA cm –2 after 2000 cycles (Figure e). As shown in Figure f, the OER activity of CeO 2 /Co 4 N displays no significant decrease after 10 h. Besides, the OER activity (Figure g) of CeO 2 /Co 4 N is comparable to or even superior to those of most reported non-noble metal electrocatalysts, suggesting the potential of alkaline OER application. …”
Section: Resultsmentioning
confidence: 77%
“…(f) I–t curves of CeO 2 /Co 4 N at 318 mV. (g) Comparison with the overpotentials of the reported OER electrocatalysts at 10 mA cm –2 . …”
Section: Resultsmentioning
confidence: 99%
“…These characteristics indicated that CNTs/CNFs are promising catalysts for MFCs applications. Yoon et al [77] demonstrated the CoOx@CoNy/NCNF550-catalyst-coated MEA used for ORR application. Figure 7a illustrates the fabrication processes of CoOx@CoNy/NCNFs achieved at various nitridation temperatures.…”
Section: Carbon Nanofiber-based Electrode Materialsmentioning
confidence: 99%